2013
DOI: 10.1007/s00330-013-3050-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of hyperattenuation of adrenal glands on contrast-enhanced computed tomography of polytraumatised patients

Abstract: • Hyperattenuating adrenal glands can be observed in 6.2% of polytraumatised patients. • Hyperattenuating adrenal glands indicate poor clinical outcome in polytraumatised patients. • In polytraumatised patients, hyperattenuating adrenal glands are associated with a high mortality rate. • Adrenal enhancement is higher amongst patients who died than amongst survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Data for differences between AUC and significance levels for comparison (p) Absolute adrenal radiodensities in the portal venous phase can also be used to predict patients' mortality with slightly lower power for prediction (MCC 0.64-0.71). As applied in previous studies [10,11], the adrenal-to-IVC ratio was less suitable for mortality prediction, especially if a suggested adrenal-to-IVC ratio of 1 was applied.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Data for differences between AUC and significance levels for comparison (p) Absolute adrenal radiodensities in the portal venous phase can also be used to predict patients' mortality with slightly lower power for prediction (MCC 0.64-0.71). As applied in previous studies [10,11], the adrenal-to-IVC ratio was less suitable for mortality prediction, especially if a suggested adrenal-to-IVC ratio of 1 was applied.…”
Section: Discussionmentioning
confidence: 93%
“…Several study groups defined adrenal enhancement as bilateral adrenal attenuation values higher than those of the inferior vena cava (IVC) [2][3][4][5][7][8][9][10][11]. Boos et al [10] and Schek et al [11] showed that adrenal enhancement is associated with a poor outcome. However, Schek's and Boos' inclusion of the IVC in their definition of hyperattenuating raises questions about IVC's suitability as a reference region.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, hematomas tend to decrease in size and attenuation, although adrenal enlargement can be observed in the first few weeks following trauma (36). Within weeks to months, the hematomas decrease in size tending to become centrally hypoattenuating.…”
Section: Ct Featuresmentioning
confidence: 99%
“…Normally the density of the adrenal glands in contrastenhanced computed tomography (CT) equals the density of other solid abdominal organs such as liver or spleen and is decreased compared to the inferior vena cava (IVC). Density measurements of the adrenal glands are often performed to evaluate adrenal masses [5], but only a few studies have focused on adrenal enhancement in critically ill patients [4,6]. In a recent study, Schek et al [6] demonstrated an association of hyperattenuating adrenal glands with a higher mortality in polytraumatized patients, indicating that hyperattenuation of the adrenal glands might be considered as a predictor of poor clinical outcome.…”
Section: R Esum Ementioning
confidence: 99%